Publisher Correction: A cdk1 gradient guides surface contraction waves in oocytes - Johanna Bischof (Nature Portfolio, 2018)
A Supplementary Information file from a different paper was inadvertently published with the original version of this Article. This file was replaced with the correct Supplementary Information file on 24 October 2017.